'It's the economy, stupid': when new politics parties take on old politics issues. Issue 4 (7th June 2021) - Spoon, Jae-Jae; Williams, Christopher J.
Abstract: Green parties have been quintessential issue owners since their founding. In recent national and European elections, however, these parties have begun to emphasize additional issues. This article seeks to understand when the greens expand their issue focus to talk about economic issues. It develops a theory of issue expansion which posits that the greens' issue expansion is related to both party competition and economic context. In particular, it posits that the size of the radical-left party and the rate of unemployment influence the degree to which green parties focus on the economy in their election manifestos. It then tests the theory on a dataset of European green parties which have run in national elections between 1981 and 2017 in 14 West and East European countries. The findings have important implications for understanding party competition in general and the issue evolution of new politics parties more specifically.